Demonstration of non-Markovian process characterisation and control on a quantum processor - G. A. L. White (Nature Portfolio, 2020)
As quantum computing devices become more complex, they enter the realm of correlated noise, which is difficult to characterise and mitigate. Here, the authors demonstrate, over a range of superconducting devices, a method for non-Markovian dynamics characterisation based on the process tensor framework.